SEROLOGICAL AND MOLECULAR CHARACTERIZATION OF CUCURBIT APHID BORNE YELLOWS VIRUS AFFECTING SQUASH, CUCUMBER AND ARABLE WEEDS IN SAUDI ARABIA - Mohammed A. Al-Saleh; Ibrahim Al-Shahwan; Zaheer Khalid; Muhammad Taimoor Shakeel; Mahmoud A. Amer (Journal of Animal and Plant Sciences, 2025)
Cucurbit aphid-born yellows virus (CABYV) is one of the primary plant viruses that cause yellowing disease of cucurbits that result in severe outbreaks leading to significant crop losses in Saudi Arabia's cucurbit crops. Implementing a comprehensive detection program to monitor the prevalence, distribution, and genetic diversity of CABYV populations in different cultivated and arable weed plant species would help implement management measures against this disease. This study aimed to identify CABYV infection in Saudi Arabia's cucumber, squash, and some arable weed hosts. A total of 50 cucumber, 38 of squash, and 27 samples of four distinct arable weeds, Chenopodium murale, Malva parviflora, Solanum nigrum, and Sonchus oleraceous were collected in the months of January to March of 2014-2015. Samples from several locations in the Riyadh region of Saudi Arabia were collected, and there were signs of a probable viral infection, such as interveinal chlorosis, yellowing symptoms, and chlorotic lesions resulting in total leaf yellowing.According to the obtained results, Cucurbit aphid-borne yellows virus (CABYV) was detected in cucumber (30 out of 50) and squash (29 out of 38), weed plant species (12/27) growing adjacent to cucumber fields using ELISA test. RT-PCR confirmed the occurrence of CABYV in cucumber, squash, and weed plants using a primer pair that is specific to the coat protein gene. The results revealed identical-sized CABYV CP gene segments (600 bp). Following partial nucleotide sequencing of the Saudi isolates of CABYV, the following accession numbers were uploaded to NBCI: MH192385 (CaBYV-SA-Cucumber), MH192386 (CaBYV-SA-Squash-1), MH192387 CaBYV-(SA-Squash-2), MH192388 (CaBYV-SA-Ch. Murale), MH192389 (CaBYV-SA-S. nigrum), MH192390 (CaBYV-SA-S. oleraceus), and MH192391 (CaBYV-SA-M. parviflora).BLAST and phylogenetic analysis showed that CABYV isolates from Riyadh region possess 98-100% identity among them, whereas their nucleotide sequence shows 93.3-100% identity with sequences of isolates deposited in NCBI.
Keywords: CABYV; Weeds; Symptoms; ELISA; RT-PCR; Sequence.